Nunukan Chicken: Genetic Characteristics, Phenotype and Utilization - Sartika, Tike; Sulandari, Sri; Zein, M S A; Paryanti, Sri (Indonesian Animal Sciences Society, 2006)
Nunukan chicken is a local chicken from East Kalimantan which spreads out in Tarakan and Nunukan Islands . The chicken has a specific buff color and Columbian type feather and also has very late feathering (VLF) trait . The Nunukan cocks and hens have no wing and tail primary feather; the tail feathers are short and fragile . The VLF trait is known to have association with a K gene on the Z chromosome. The chicken is efficient in protein metabolism . Sulfur amino acids (cystine and methionine) that needed for feather growth, could be utilized for meat and egg production . The egg production of Nunukan chicken was better than the Kampung chicken . The average of hen day, hen house and peak production of Nunukan chicken was 45 . 39.1 and 62%, respectively, while the Kampung chicken was 35 .9, 30 .9 and 48%, respectively . Based on genetic analysis, the external genotype characteristic of the Nunukan chicken is ii ce ss Idld pp. It means that the phenotype appearance of the Nunukan chicken was columbian and gold feathering type, yellow and white shank color and single comb type. This phenotype is similar to Merawang Chicken . The genetic introgression of the Nunukan chicken is affected by the Rhode Island Red with the genetic introgression value of 0.964 . Key words: Nunukan chicken, character, genetic; phenotype characteristics, utilization